2011
DOI: 10.1007/s13594-011-0045-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity of the traditional Iranian cheeses Lighvan and Koozeh, as revealed by polyphasic culturing and culture-independent approaches

Abstract: The microbiota of two traditional Iranian cheeses (Lighvan and Koozeh) made of raw ewe's milk or mixtures of ewe's and goat's milk without starter addition was explored by culture-independent and culture-dependent approaches. Three batches of Lighvan and one of Koozeh were subjected to culture-independent polymerase chain reaction (PCR)-denaturing gradient gel electrophoresis (DGGE) analysis and sequencing of dominant bands to assess the microbial structure and dynamics through manufacturing and ripening. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…They showed that the Lactobacillus plantarum was the dominant strain in the Beyaz cheese (21). A study performed by Edalatian et al, (2012) on the Koozeh cheese, isolated Lactobacillusplantarum, Lactobacillusbrevis, Lactobacillus hlavaty, Lactobacillus delbrueckii, Lactobacillus fermentum, and Lactobacillus ferment from this cheese and showed that the Lactobacillus plantarum was the dominant strain (8). Hasanzad Azar and Ehsani (2013) reported that the plantarum strain was the dominant strain in the Coupe local cheese (22).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They showed that the Lactobacillus plantarum was the dominant strain in the Beyaz cheese (21). A study performed by Edalatian et al, (2012) on the Koozeh cheese, isolated Lactobacillusplantarum, Lactobacillusbrevis, Lactobacillus hlavaty, Lactobacillus delbrueckii, Lactobacillus fermentum, and Lactobacillus ferment from this cheese and showed that the Lactobacillus plantarum was the dominant strain (8). Hasanzad Azar and Ehsani (2013) reported that the plantarum strain was the dominant strain in the Coupe local cheese (22).…”
Section: Discussionmentioning
confidence: 95%
“…Coupe cheese is prepared using rennet cheese and without adding any starters. The Coupe cheese structure is granular and dry (8). Traditional yogurt is prepared using yogurt as the starter (9).…”
Section: Introductionmentioning
confidence: 99%
“…The 96 isolates have already been typed by the repetitive extragenic palyndromic (rep-PCR) technique and found to consist in 57 diVerent proWles representing distinct strains [9]. In spite of this, isolates were all analyzed for the production of inhibitory compounds because large phenotypic variations have been reported among genetically indistinguishable strains [4,27].…”
Section: Resultsmentioning
confidence: 99%
“…Large numbers have been repeatedly reported in curd and ripened cheeses made from raw milk (10 4 -10 6 and 10 5 -10 7 cfu.g ¡1 , respectively) [4,15,30]. Further, enterococcal species have recently been shown to be the dominant cultivable populations of the traditional Iranian cheeses Lighvan and Koozeh [9]. Some authors believe enterococci responsible for producing the typical taste and Xavor of certain foods [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…focused on Enterococcus faecium; first, for its availability in our local animals milk, second as mentioned by Sevec et al,(15) the dominant end product is Llactic acid and third, for the few studies in Iraq concerning with it.Kalhotka et al,(16) isolated Enterococcus faecium, E. mundtii, E. durans from9 samples of goat milk and cheeses. In the study of Edalatian et al,(17) traditional Iranian cheeses (Lighvan and Koozeh) made of raw ewe's milk or mixtures of ewe's and goat's milk has been studied, and Enterococcus faecium and Enterococcus faecalis were found to be dominant among the isolates in all batches.…”
mentioning
confidence: 99%